The list - Berry, Steve, 1955- (Grand Central Publishing, 2025)
"Brent Walker is returning home to Concord, a quaint town in central Georgia nestled close to the Savannah River. Ten years ago, after the sudden death of his wife, Brent closed his law practice, said goodbye to his parents, and moved three hundred miles away to a self-imposed exile. His father died two years ago, and now Brent's coming back to take care of his ailing mother, hired by Southern Republic Pulp and Paper Company as an assistant general counsel. For decades Southern Republic has invested heavily in Concord, building a paper mill and creating a thriving community, one where its employees live, work, and retire. Unlike countless other mills that have closed Southern Republic survived, becoming a model for the paper industry. But Southern Republic's success is based largely on something called the Priority program, a highly unorthodox way to secretly control costs, one that provides a huge edge over its competition. Only the three owners of the company are aware of the program's existence, but one of them, Christopher Bozin, has had a change of heart. Brent's return to Concord, a move Bozin personally orchestrated, provides a chance at redemption that Bozin desperately wants before cancer takes his life. So a plan is set into motion-one that will not only criminally implicate Bozin's two partners-it will also place Brent Walker right in the crosshairs of men who want him dead. With only one course left available: Find and reveal the shocking secret of the list." -publisher.